Метод динамічного формування структури рівня радіодоступу для мереж 5G - Гуськов, П. О.; Максимюк, Т. А.; Климаш, М. М. (Видавництво Львівської політехніки, 2015)
Розглянуто концепцію гнучкого функціонального роздвоєння протокольного стека між центральною платформою керування та локальними точками радіодоступу у вигляді програмної платформи для координованого керування рівнем радіодоступу. Запропоновано метод динамічного формування структури мережі радіодоступу перепризначенням контролеру безпровідного кластера та реконфігурації транспортної підсистеми, що дає змогу підвищити ефективність функціонування безпровідного кластера та досягти вищих показників пропускної здатності без застосування додаткових RAP. Nowadays, plenty of smart phones and tablets result in increased demands for bandwidth and availability of mobile networks. According to recent studied, 5G is expected to bring significant improvement such as 10-100-fold peak data rates, 1000-fold network capacity and 10-fold energy efficiency. There are two key enablers of these requirements: ultra-dense deployment of small cells and centralized signal processing. In this paper, we focus on flexible and adaptive management for 5G mobile networks. We propose the dynamic RAN (Radio Access Network) synthesis method that includes two main stages: reassignment of the WCM (Wireless Cluster Management) controller and dynamic backhaul reconfiguration. Former increases the performance of wireless cluster, while backhaul remains unchangeable that allows to decrease the RAN convergence time. The latter allows to improve capacity of backhaul links by virtualization and topology modifying. In addition, proposed system exploits flexibilities of backhaul network technologies to adapt the backhaul network to requirements of RAN. Further insights show that backhaul properties play an important role in future radio access networks with cooperation of radio access points. Modern optical backhaul networks cannot guarantee that cooperation techniques will be applied ubiquitously in radio access networks. Hence, new cooperation techniques and algorithms must rely not only on the information from the RAN, but also incorporate the conditions of backhaul and core network. Simulation results showed that the proposed method drastically increases the feasibility of wireless cluster, especially in high-load scenarios and enables to achieve higher performance capacity without using additional RAP. It has showed that with the increasing number of active users within the cluster the proposed method allows to get higher levels of cluster feasibility through effective adaptation of the RAN structure according to the users’ requirements.
Method of dynamic ran synthesis for 5G networks
Keywords: 5G; C-RAN; NFV; безпровідний кластер; wireless cluster